A gravity current study within the Palma de Mallorca basin - Martínez, Daniel; Cuxart, Joan (Física de la Tierra, 2008)
An analysis of a katabatic flow is made through data provided by a high resolution mesoscale simulation of the isle of Majorca in the western Mediterranean sea. It is found that a quasi-steady state is reached in the second part of the night and that the katabatic flow interacts with a cold pool formed at the end of the slope, in the center of the Palma basin. The application of a two-layer model following the framework set out in Mahrt (1982) shows that the main term of the momentum budget equation is the buoyancy force, which is generally balanced by the stress divergence and the advection term. The entrainment at the top is small and the scale analysis shows that the flow is in a shooting regime, in agreement with the hydraulic theory. Finally, an oscillatory behaviour of the wind speed and potential temperature is well correlated with the changes in the slope angle and it is adapted with the waves generated above in the lee side of the mountain.